Playing with Strangeness: Principles of Designing Action Scenarios to Promote Creativity in Children. - Blanco, Vicente; Cidrás, Salvador; Freire, Estella (International Journal of Art & Design Education, 2025)
As artists and teachers in a Teacher Training Faculty, we have designed proposals for children that transfer our own experience as creators in the studio to the educational field. In this way, the classroom is configured into a versatile workplace, like the studio, allowing us to carry out and analyse different workshops for children with the aim of promoting creativity. These workshops, which we call 'action scenarios' take as references the different processes of creating materials and toys for children used by twentieth‐century western artists. This research reflects on the design and implementation of these scenarios with the aim of identifying a series of principles or parameters that can help pre‐school and primary school teachers plan, design and distinguish creative proposals in the visual arts. Four principles are identified: play as a principle of exploration, estrangement as an aesthetic principle, doing as a principle of thinking and cooperation as a principle of possibility. These principles are conceived as a flexible tool to explore and understand creativity in the educational field, especially among education professionals without training in the visual arts.